Diseño e implementación de un sistema de movimiento para el proceso de deshidratación de órganos animales en alcohol (2023)
Plastination is a technique or process used for the preservation of anatomical components. It is based on exchanging liquids of the tissues (water and lipids) by a polymer (silicon, epoxy resin or polyester) under special conditions, as a result organs with a real appearance and physical properties (flexible or stable), that allow their manipulation, are obtained. The technique consists of four fundamental stages, which are: first, fixation stage; second, dehydration stage; third, forced impregnation stage and fourth, curing stage. The present study aims to design and implement a semi-automatic system to optimize the dehydration process of animal tissues and organs using pumps and control systems. For the correct implementation of the second stage, that of dehydration, a follow-up was carried out by means of the values of the concentration of alcohol (%) obtained from the alcoholometer, which is constituted of a density meter and movement sensors (infrared sensors). Each time ethyl alcohol decreases its concentration down to 65 or 60%, alcohol must be added again until it reaches 70%, which is its maximum concentration, and that is how it is verified that the technique is working correctly. Therefore, the stage is over when ethyl alcohol has been added several times and the alcohol concentration no longer decreases.